2009
DOI: 10.1021/ma900958a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Branched Methacrylic Copolymers: Observation of Near-Ideal Behavior using RAFT Polymerization

Abstract: We report the synthesis of model highly branched methacrylic copolymers by copolymerizing methyl methacrylate (MMA) with a disulfide-based dimethacrylate (DSDMA) branching comonomer via reversible addition-fragmentation chain transfer (RAFT) in toluene at 90°C using 1,1 0 -azobiscyclohexanecarbonitrile initiator and a cumyl dithiobenzoate (CDB) chain transfer agent. Selective cleavage of the disulfide bonds in the DSDMA branching comonomer using tributylphosphine leads to the formation of low polydispersity pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
153
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(161 citation statements)
references
References 33 publications
7
153
0
1
Order By: Relevance
“…Although such high conversions are generally not advisable for RAFT macro-CTA syntheses, in this case it is essential because copolymerization of the second (pendent) methacrylate group on the DSDMA comonomer only occurs at high conversions. 32 A number-average molecular weight (M n ) of 14,000 g mol -1 and a reasonably low M w /M n of 1.26 was recorded for the G 54 -D 0.50 macro-CTA, indicating good RAFT control. A small high molecular weight shoulder was observed in the chromatogram, which was ascribed to a low level of branching for this statistical copolymer.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although such high conversions are generally not advisable for RAFT macro-CTA syntheses, in this case it is essential because copolymerization of the second (pendent) methacrylate group on the DSDMA comonomer only occurs at high conversions. 32 A number-average molecular weight (M n ) of 14,000 g mol -1 and a reasonably low M w /M n of 1.26 was recorded for the G 54 -D 0.50 macro-CTA, indicating good RAFT control. A small high molecular weight shoulder was observed in the chromatogram, which was ascribed to a low level of branching for this statistical copolymer.…”
Section: Resultsmentioning
confidence: 97%
“…The first route involves statistical copolymerization of a bifunctional disulfide-based methacrylic monomer (DSDMA) with GMA during the macro-CTA synthesis. [31][32][33] Recently, we reported that, when copolymerized with a monofunctional methacrylic monomer in sufficiently dilute solution, DSDMA undergoes intramolecular cyclization rather than intermolecular branching. 29 Subsequent disulfide cleavage produces two 2-thioethyl methacrylate residues on the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in spite of the fact that the synthetic strategies applied deliver poorer control over the molecular structure of these hyperbranched polymers when compared to "true" dendrimers, the economic and practical advantages from adopting these strategies are generally gained without significant negative impact upon the desired beneficial/differentiated material properties. 1,[3][4][5][6][7][8][9][10][11][12] In addition, these more affordable and accessible approaches have led to significant industrial interest targeted towards using these materials in larger scale applications such as imaging agents, reactive resins and industrial coatings. 1,[13][14][15] Compared to linear polymers, highly/hyper branched polymers often exhibit improved solubility, lower (melt) viscosity, higher density of functional-groups and have a more compact/globular structure.…”
Section: Introductionmentioning
confidence: 99%
“…solventless), controlled ROP mechanism. [3][4][9][10][11][12][31][32][33][34][35][36][37][38][39][40] The 'Strathclyde Method' was a pivotal early example of such a branching synthetic strategy and centred on the standard free radical (SFR) copolymerisation of monofunctional and difunctional vinyl monomers. [9][10][11][12] One of the main conclusions drawn from this work was that gelation, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation